(untitled) (Journal of Educational Sciences, 2016)
The article provides a structural-functional analysis of the implementation of educational programmers of the subject «Self-knowledge» of the state program of moral education in the education system of the Republic of Kazakhstan. Problem analysis covers the period from the inception of the Fund «Bobek» and up to the present time. Considered the formation of the charity Fund «Bobek» and the periods of its development: the first period 1992-2000 years, the second period 2000-2010, the third period is 2010 – present. The author analyzes the work of the charity Fund «Bobek», which was created in order to ensure social protection of children of preschool age, their education and full development, and stresses the importance of the Fund in the beginning of its development. From the very beginning Fund special attention was paid to the protection and development of children-orphans, improve their health and prevention of social deviations adaptation of children in society. The article describes the content and structural the features of the program of moral education «Selfcognition » as one of the activities of the Fund «Bobek». Today, the name of the Fund was renamed the national scientific-practical, educational and health center «Bobek».In the experimental course «Self-cognition» passed all the levels of testing and implementation in secondary school. Practice has shown that it was necessary for the implementation of this discipline as one of the compulsory subjects in the education system. In the article the introduction of the course «Self-cognition at all levels of the education system that has created the necessity of opening a new specialty and the traini ng of future teachers «Self- cognition» of our country.